Different Compost Materials Used as Source of Organic Matter in Production of Chili Pepper - Sumbayak, Roy S.O.; Handajaningsih, Merakati; Hartal, Hartal; Marwanto, Marwanto (Akta Agrosia, 2019)
Compost has been commonly used as the primary organic matter in organic plant production, especially in vegetable production.  Different sources of compost materials give different medium structures and chemical characteristics. The objectives of this research were: 1) to evaluate the response of growth and yield of chili pepper to a rate of compost and source of animal waste which were used as compost; 2) to determine the optimum rate of fertilizer for the highest growth and yield of chili pepper. The research was carried out from November 2015 until March 2016. Compost material treatments consisted of cow dung, empty palm oil bunches, and mixed of vegetable residue and weeds. The compost rate treatments consisted of 0 ton ha-1, 10 ton ha-1, 20 ton ha-1, and 30 ton ha-1. No interaction between the two treatments was found to influence plant growth and yield variables.   The type of compost materials affected plant height of 5, 6, and7 weeks after transplanting.  Cow dung as a source of compost showed the best effect in increasing chili plant height.  Plant height, the number of plant dichotomous, and plant canopy responded linearly  to the increase of the compost rate. The usage of compost at 20 ton ha-1 and 30 ha-1 resulted in higher fruit length, the number of fruit, and fruit weight per plant.   Keywords: chili pepper, compost, organic, growth, yield